TPACK Research in Scopus and Web of Science: A Bibliometric Analysis from 2018 to 2022 - Iftitah, Khofifa Najma; Permatasari, Anggraeni Dian (Universitas Muhammadiyah Surakarta, 2023)
This study is to determine TPACK research from 2018-2022 with bibliometric analysis using the Scopus and Web of Science databases. The method used is PRISMA and the application used in analyzing is Bibliomterix R. Based on the results of the bibliometric analysis that has been carried out on 1094 publications of articles, proceedings papers, and books. It was found that there was a consistent increase in publications every year from 2019 to 2022. It is also obtained that the authors with the most publications are Chai CS and Zhang H, and the most impactful author is Chai CS. The publications of Shulman and Misrha became the most influential co-citation. Indonesia is the country with the most TPACK publications and the United States is the most cited country. The most relevant journal is Journal of Physics: Conference Series and Education and Information Technologies for Impactful Source. Research that can be further developed on TPACK (research that teaching rarely does) includes technological pedagogical content knowledge, engineering education, people, articles, and teachers. And the last trending topic is people, articles, and learning.